2012
DOI: 10.4103/1817-1737.91558
|View full text |Cite
|
Sign up to set email alerts
|

Study of the association between −403G/A and −28C/G RANTES gene polymorphisms and asthma in Lebanon

Abstract: CONTEXT:Asthma is a complex inflammatory condition often associated with bronchial hyper reactivity and atopy. Genetic and environmental factors are implicated in the etiopathogenesis of asthma. Regulated upon Activation Normal T- cell Expressed and Secreted (RANTES) is a CC chemokine responsible for the recruitment of inflammatory cells, suggesting a possible role for this chemokine in asthma. Both -403A and -28G alleles of the RANTES promoter region were found to be associated with asthma/atopy in some but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In other countries, both −403G/A and −28C/G polymorphisms did not have a detectable effect on asthma susceptibility in African Americans, Lebanon, Spanish or Budapest population, respectively [12], [18], [25], [27]. However, Lachheb et al [23] suggested that both polymorphisms may play an important role in asthma predisposition, airway obstruction severity, or bronchial hyperresponsiveness among Tunisian or Korean children.…”
Section: Discussionmentioning
confidence: 95%
“…In other countries, both −403G/A and −28C/G polymorphisms did not have a detectable effect on asthma susceptibility in African Americans, Lebanon, Spanish or Budapest population, respectively [12], [18], [25], [27]. However, Lachheb et al [23] suggested that both polymorphisms may play an important role in asthma predisposition, airway obstruction severity, or bronchial hyperresponsiveness among Tunisian or Korean children.…”
Section: Discussionmentioning
confidence: 95%
“…There have been limited studies on T2DM among the global population that has been associated with lower and higher risk ( Böger et al, 2005 , Herder et al, 2008 , Kochetova et al, 2019 , Lee et al, 2021 , Prasad et al, 2007 ) and our study was highly associated with an average risk × 4.3. Consequently, the variant rs2107538 has been studied in various human diseases such as GDM ( Teler et al, 2017 ), PTDM ( Joo et al, 2007 , Jeong et al, 2010 ), cardiovascular ( Mohtavinejad et al, 2021 ) and coronary artery diseases ( Lee et al, 2021 , Ting et al, 2015 , Liu et al, 2012 , Duell et al, 2006 ), myocardial infarction ( Tereshchenko et al, 2011 ), asthma ( Nahas et al, 2012 , Lu et al, 2012 ), prostatic hyperplasia ( Pang et al, 2019 ), and cancers such as prostate cancer ( Kidd et al, 2012 ), oral and pancreatic cancers ( Weng et al, 2010 , Duell et al, 2006 ). Furthermore, these variants were studied in meta -analyses alongside tuberculosis ( Sheng and Qi, 2020b ) and cancer ( Ying et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%